Comparative Evaluation of Chiglitazar and Sitagliptin on the Levels of Retinol-Binding Protein 4 and Its Correlation With Insulin Resistance in Patients With Type 2 Diabetes - Zhou, Yunting; Wang, Huiying; Wang, Yuming; Xu, Xiaohua; Li, Fengfei; Zhou, Junming; Shan, Ting; Huang, Rong; Cai, Tingting; Liu, Xiaomei; Su, Xiaofei; Li, Huiqin; et al. (Frontiers in Endocrinology, 2022)
Aims: We evaluated the efficacy and significant changes in the levels of retinol-binding protein 4 (RBP-4) and insulin resistance in patients with type 2 diabetes mellitus (T2DM) treated with chiglitazar versus sitagliptin. Methods: Eighty-one T2DM patients with haemoglobin A1c (HbA1c) level of 7.5%–10.0% were selected. Based on the study criteria, patients were randomly assigned to receive chiglitazar (32 mg), chiglitazar (48 mg), or sitagliptin (100 mg) orally for 24 weeks. Sociodemographic and anthropometric characteristics, lipid profiles, glucose profiles, and serum RBP-4 levels were determined at baseline and at the end of the therapy. Results: After treatment for 24 weeks, significant changes in fasting blood glucose (FBG), fasting insulin (Fins), 2 h-blood glucose (2h-BG), the score values of insulin resistance/insulin secretion/β cell function (HOMA-IR, HOMA-IS, and HOMA-β), triglyceride (TG), free fatty acid (FFA), high-density lipoprotein cholesterol (HDL-C), and RBP-4 levels were detected in patients with chiglitazar administration and sitagliptin administration. Changes in RBP-4 levels were positively correlated with changes in HOMA-IR and 2 h-BG in linear regression. Conclusions: Chiglitazar showed a greater improvement in parameters of diabetes than sitagliptin, and changes in serum RBP-4 levels were associated with changes in insulin-sensitizing parameters.